PENATAUSAHAAN KEUANGAN DESA DALAM RANGKA PENYUSUNAN LAPORAN PERTANGGUNGJAWABAN - Siti Maghfiroh; Bambang Agus Pramuka (Jurnal Pengabdian Bisnis dan Akuntansi Soedirman (JPBA), 2022)
Village finance is all rights and obligations in the context of organizing village government that can be valued with money, including all forms of wealth related to the rights and obligations of the village. Village finances come from the original income of the village, apbd, and apbn. The allocation of village funds from the regional budget is an instrument to build and restore trust in state management in Indonesia. In order to support the realization of good governance in village administration, village financial management is carried out based on the principles of governance, namely transparent, accountable and participatory and is carried out in an orderly and budgetary discipline. For this reason, good financial management is needed. Law Number 6 of 2014 concerning Villages, Article 93 paragraph (1) states that village financial management includes: planning, implementing, administering, reporting, and accountability. In order for the Village Finance Management to be carried out properly, it must be supported, among others, by competent and qualified human resources as well as adequate financial systems and procedures. Therefore, this community service is carried out for tambaksari kidul village officials, Kembaran district, Banyumas regency, so that village officials have the competence and skills to manage finances. The results of this devotion can provide knowledge for the village apparat.